Renin-Angiotensin System Blockade Improves Cardiac Indices in Acromegaly Patients - Thomas, Julia D. J.; Dattani, Abhishek; Zemrak, Filip; Burchell, Thomas; Akker, Scott A.; Kaplan, Felicity J. L.; Khoo, Bernard; Aylwin, Simon; Grossman, Ashley B.; Davies, L. Ceri; Korbonits, Márta (Experimental and Clinical Endocrinology & Diabetes, 2017)
Blockade of the angiotensin-renin system, with angiotensin converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARBs), has been shown to improve cardiac outcomes following myocardial infarction and delay progression of heart failure. Acromegaly is associated with a disease-specific cardiomyopathy, the pathogenesis of which is poorly understood.The cardiac indices of patients with active acromegaly with no hypertension (Group A, n=4), established hypertension not taking ACEi/ARBs (Group B, n=4) and established hypertension taking ACEi/ARBs (Group C, n=4) were compared using cardiac magnetic imaging.Patients taking ACEi/ARBs had lower end diastolic volume index (EDVi) and end systolic volume index (ESVi) than the other 2 groups ([C] 73.24 vs. [A] 97.92 vs. [B] 101.03 ml/m2, ANOVA p=0.034, B vs. C p<0.01). Groups A and B had EDVi and ESVi values at the top of published reference range values; Group C had values in the middle of the range.Acromegaly patients on ACEi/ARBs for hypertension demonstrate improved cardiac indices compared to acromegaly patients with hypertension not taking these medications. Further studies are needed to determine if these drugs have a beneficial cardiac effect in acromegaly in the absence of demonstrable hypertension.
Keywords: pituitary; acromegaly; cardiac magnetic resonance; renin-angiotensin